1991
DOI: 10.1073/pnas.88.23.10946
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoprotein complex formed between herpes simplex virus UL9 protein and the origin of DNA replication: inter- and intramolecular interactions.

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…To date, attempts to develop an origin-directed in vitro HSV-1 DNA replication system have been unsuccessful (14,39), indicating that the seven viral replication proteins, although essential for viral DNA replication in infected cells, are insufficient for origin-driven DNA synthesis outside the cellular milieu. Therefore, as in other viral systems, cellular proteins may be required at one or more steps in HSV-1 DNA replication.…”
Section: Nf-i Is Involvedmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, attempts to develop an origin-directed in vitro HSV-1 DNA replication system have been unsuccessful (14,39), indicating that the seven viral replication proteins, although essential for viral DNA replication in infected cells, are insufficient for origin-driven DNA synthesis outside the cellular milieu. Therefore, as in other viral systems, cellular proteins may be required at one or more steps in HSV-1 DNA replication.…”
Section: Nf-i Is Involvedmentioning
confidence: 99%
“…Single copies of two other sequences containing OBP binding sites which are highly homologous to site I-sites II and III-are also found within oriS (Fig. 1B), while two copies of site III are found in oriL (9,15,17,19,24,29,37,39,48,49). The limits of sites I and II were defined by DNase I footprinting of partially purified OBP (17,18,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Nterminal part of the protein is also necessary for efficient dimerization (Elias et al, 1992) and for the observed cooperativity in binding to ori s (Elias et al, 1990(Elias et al, , 1992Hazuda et al, 1992). Interactions involving this region probably also account for the ability of UL9 to distort and/or form complex nucleoprotein structures at the origin (Koffet aI., 1991 ;Rabkin & Hanlon, 1991 ;Fierer & Challberg, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Although the helicase assay utilizes model substrates, this finding m a y nevertheless be relevant to the way in which U L 9 functions at viral replication origins. Previous studies have indicated that sequence-specific binding of U L 9 to the viral replication origins results in the formation of higher- order nucleoprotein structures (Rabkin & Hanlon, 1991) and that distortion and wrapping of the DNA occurs under these conditions (Elias et al, 1990;Koff et al, 1991;Hazuda et al, 1992;Fierer & Challberg, 1992). The helicase-associated DNA-binding activity of UL9 molecules within the nucleoprotein complex may then allow interaction with such regions of DNA and subsequent energy-dependent unwinding of the DNA duplex.…”
mentioning
confidence: 99%